ANALISIS PERENCANAAN PEMBANGUNAN DAERAH DAN ANGGARAN DI KABUPATEN NAGAN RAYA - Ahmad Ferizal; Helmi Noviar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
This study intends to find out how good planning and budgeting is and aims to see the performance of the Nagan Raya Regency Legislative Council (DPRK). In the 2021 Nagan Raya Regency RPJMK Document, in the process of compiling the Nagan Raya Regency RPJMK Document, there are systemic complexities of problems. To fix this problem, a Soft System Methodology (SSM) approach is used. The calculation of activities that are not synchronized between planning and activities and budgets carried out by detailed interviews. Obtaining conformity shows the compatibility between planning and budgeting activities in the Nagan Raya Regency People's Representative Council. The best fit is in POKIR for Community welfare. Where in POKIR explains about, which village and what development is being carried out as well as how much is the budget/cost of the development. The results of the analysis of performance achievement in the Bappeda of Nagan Raya Regency. Sometimes there are obstacles that make the Program not suitable due to field events such as late Disbursement of Funds, the Programs and activities have not been according to the time set so that they are less consistent. The results of the analysis of performance achievements in the Nagan Raya Regency People's Representative Council show that both targets, programs and activities are in line with the predetermined targets.